A recombinant antibody with the antigen-specific, major histocompatibility complex-restricted specificity of T cells. - Andersen, P S (1996)
Specific recognition of peptide/major histocompatibility complex (MHC) molecule complexes by the T-cell receptor is a key reaction in the specific immune response. Antibodies against peptide/MHC complexes would therefore be valuable tools in studying MHC function and T-cell recognition and might lead to novel approaches in immunotherapy. However, it has proven difficult to generate antibodies with the specificity of T cells by conventional hybridoma techniques. Here we report that the phage display technology is a feasible alternative to generate antibodies recognizing specific, predetermined peptide/MHC complexes.